2012
DOI: 10.1111/j.1399-5618.2012.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Waiting to win: elevated striatal and orbitofrontal cortical activity during reward anticipation in euthymic bipolar disorder adults

Abstract: Objective Bipolar disorder may be characterized by a hypersensitivity to reward-relevant stimuli, potentially underlying the emotional lability and dysregulation that characterizes the illness. In parallel, research highlights the predominant role of striatal and orbitofrontal cortical (OFC) regions in reward-processing and approach-related affect. We aimed to examine whether bipolar disorder, relative to healthy, participants displayed elevated activity in these regions during reward processing. Methods Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
233
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(259 citation statements)
references
References 41 publications
19
233
7
Order By: Relevance
“…In contrast, several studies in non-depressed subjects with bipolar disorder have found evidence of reward system hyper-responsivity. Elevated reward system responses have been reported in both manic (Abler et al, 2008) and euthymic bipolar patients (Nusslock et al, 2012;Caseras et al, 2013). However, only one study to our knowledge has examined reward-related signaling in bipolar depression: Chase et al (2013) who did not find differences in ventral striatum prediction error responses between controls and subjects with bipolar or unipolar depression.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, several studies in non-depressed subjects with bipolar disorder have found evidence of reward system hyper-responsivity. Elevated reward system responses have been reported in both manic (Abler et al, 2008) and euthymic bipolar patients (Nusslock et al, 2012;Caseras et al, 2013). However, only one study to our knowledge has examined reward-related signaling in bipolar depression: Chase et al (2013) who did not find differences in ventral striatum prediction error responses between controls and subjects with bipolar or unipolar depression.…”
Section: Introductionmentioning
confidence: 77%
“…However, prior research suggests that bipolar patients studied during mania or euthymic states may have enhanced reward responses (Abler et al, 2008;Nusslock et al, 2012;Caseras et al, 2013). Although speculative, it is possible that patients with bipolar disorder may have tonically elevated reward system activation and connectivity, which is dimensionally blunted in depressive episodes.…”
Section: Discussionmentioning
confidence: 98%
“…Recent fMRI studies showed alterations in reward-related striatal and cortical brain activations, state-dependent, but also during euthymia (Abler et al, 2008;Caseras et al, 2013;Nusslock et al, 2012;Trost et al, 2014;Whitton et al, 2015). A number of studies have reported elevated striatal activations in response to rewarding stimuli in hypomanic individuals (O'Sullivan et al, 2011), euthymic (Mason et al, 2014;Nusslock et al, 2012) and manic (Abler et al, 2008) bipolar patients. However, other studies in bipolar patients have shown a reduced reward responsiveness challenging the hypothesis of a general reward hypersensitivity model of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of medicated patients with BD have reported increased activity in the ventral striatum (VS) during reward and affective processing (Lawrence et al, 2004;Nusslock et al, 2012;Caseras et al, 2013), and this has been interpreted as reflecting increased reward sensitivity and more generally a 'reward hypersensitivity model for BD' (Caseras et al, 2013). However, nascent data suggest ameliorative effects of antipsychotic and mood-stabilizing medications on neural activity within limbic circuits, making accurate interpretation of data from medicated individuals difficult (Haldane et al, 2008;Phillips et al, 2008;Passarotti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%